Seagull Optimization Algorithm–Based Fractional-Order Fuzzy Controller for LFC of Multi-Area Diverse Source System With Realistic Constraints - Naga Sai Kalyan, CH.; Goud, B. Srikanth; Reddy, Ch. Rami; Udumula, Ramanjaneya Reddy; Bajaj, Mohit; Sharma, Naveen Kumar; Elgamli, Elmazeg; Shouran, Mokhtar; Kamel, Salah (Frontiers in Energy Research, 2022)
This paper initiates the implementation of fractional order (FO) fuzzy (F) PID (FOFPID) controller fine-tuned using seagull optimization algorithm (SOA) for the study of load frequency control (LFC). Initially, the SOA tuned FOFPID regulator is implemented to the widely utilized model of dual area reheat-thermal system (DARTS) named as test system-1 in this work for a perturbation of 10% step load (10%SLP) on area-1. Dynamical analysis of DARTS system reveals the viability of SOA tuned FOFPID control scheme in regulating frequency deviations effectively compared to other control schemes covered in literature. Later, the presented regulator is implemented to multi area diverse sources (MADS) system possessing realistic constraints in this paper termed as test system-2. Sovereignty of presented FOFPID controller is once again evidenced with controllers of PID/FOPID/FPID fine-tuned with SOA approach. Moreover, the effect of considering practical realistic non-linearity constraints on MADS system performance is visualized. Further, AC-DC lines are incorporated with MADS system to enhance the performance under heavy load disturbances.